SYSTEMATIC LITERATURE REVIEW: DEVELOPMENT OF AGRICULTURAL MANAGEMENT ON JERUK KEPROK FARMERS IN CENTRAL ACEH REGENCY, GAYO HIGHLANDS - Haryadi Sarjono; Della Amelinda Putri (AGRIBUSINESS JOURNAL, 2025)
This study aims to determine the tangerine (orange) farmers in Central Aceh District, Gayo Highlands. The cultivation of Orange Keprok in the Gayo highlands holds strong agribusiness potential due to a suitable agroclimate, available farmland, and growing national market demand. This research uses a Systematic Literature Review to analyze relevant literature and several case studies as a development Tangerine cultivation in Central Aceh District, specifically in the Gayo Highlands. 9 literatures were evaluated from Google Scholar based on keywords ("Citrus nobilis" OR "Keprok Tangerine" OR "Jeruk Keprok") AND ("farmer profile" OR "farmer characteristics" OR "land utilization" OR "land use" OR productivity OR "fruit-bearing trees") AND ("agribusiness development" OR "agricultural solution" OR "farm management" OR "business strategy" OR "agricultural innovation"). Despite these constraints, Jeruk Keprok remains a high-potential horticultural commodity with strong market demand and considerable economic value. Overall, the study shows that the integration of local government and active participation of farmers, a productive, sustainable, and resilient citrus cultivation system in the future needs to be realized to support a more advanced citrus farming agribusiness.